2005
DOI: 10.1111/j.1365-2656.2005.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Species abundance and the distribution of specialization in host–parasite interaction networks

Abstract: Summary1. Recent studies have evaluated the distribution of specialization in species interaction networks. Species abundance patterns have been hypothesized to determine observed topological patterns. We evaluate this hypothesis in the context of host-parasite interaction networks. 2. We used two independent series of data sets, one consisting of data for seven sites describing interactions between freshwater fish and their metazoan parasites and another consisting of data for 25 localities describing interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
238
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(266 citation statements)
references
References 38 publications
22
238
0
1
Order By: Relevance
“…We analyzed two traits, interaction frequency and degree of generalization (estimated here as the average number species with which the plant and pollinator interact), which required no detailed information about the species involved, beyond knowing with how many species they interacted and how frequently (21). We chose these traits because, first, locally rare plant-pollinator interactions should be particularly susceptible to habitat reduction because any further decrease in interaction frequency, perhaps related to declining species abundance, could trigger complete disruption (22)(23). Second, interactions between plant and pollinator species with limited numbers of alternative partners (i.e., interactions of low degree) should also be particularly susceptible beyond any confounding effect of interaction frequency, because they cannot be "subsidized" or "rescued" by third parties when, for instance, interacting species become spatially or phenologically isolated from each other (4,24).…”
Section: Textmentioning
confidence: 99%
“…We analyzed two traits, interaction frequency and degree of generalization (estimated here as the average number species with which the plant and pollinator interact), which required no detailed information about the species involved, beyond knowing with how many species they interacted and how frequently (21). We chose these traits because, first, locally rare plant-pollinator interactions should be particularly susceptible to habitat reduction because any further decrease in interaction frequency, perhaps related to declining species abundance, could trigger complete disruption (22)(23). Second, interactions between plant and pollinator species with limited numbers of alternative partners (i.e., interactions of low degree) should also be particularly susceptible beyond any confounding effect of interaction frequency, because they cannot be "subsidized" or "rescued" by third parties when, for instance, interacting species become spatially or phenologically isolated from each other (4,24).…”
Section: Textmentioning
confidence: 99%
“…Many of them have distribution patterns that are related to dispersal, behaviour, physiology and interactions with other species (Krebs 2001). Parasite distribution is determined by the same factors, but they are also strongly affected by the presence and abundance of their hosts (Vázquez et al 2005). Therefore, the abundance and prevalence of parasites usually shows spatial and seasonal variation, which may result in local or regional patterns (e.g., Poulin 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that species abundance has a major role in determining how interactions are structured in different ecological networks, including positive interactions such as plant-pollinators [9,14] and plant-plant facilitation [15], commensalistic interaction among epiphytes and phorophytes [16] or antagonisms between plant-herbivores and hosts-parasitoids [12,17]. These studies also showed that the observed interactions are better predicted by simulations when other factors are included together with the abundance, such as phenological overlap [9,11,12], morphological matches among species [14] or the phylogenetic relationship, which ultimately influences the traits of the species [15].…”
Section: Introductionmentioning
confidence: 99%